2011
DOI: 10.1227/neu.0b013e318208f5e0
|View full text |Cite
|
Sign up to set email alerts
|

Evans' Index Revisited: The Need for an Alternative in Normal Pressure Hydrocephalus

Abstract: Evans' index value can vary significantly in a patient with NPH, depending on the level of the brain CT scan image at which the frontal horns and maximal inner skull diameters are measured. Evans' index is not an ideal method for estimating the VV in NPH patients. Volumetric measurements represent the logical accurate estimate of true ventricular size as well as the size of the other intracranial compartments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
116
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(134 citation statements)
references
References 18 publications
4
116
1
6
Order By: Relevance
“…He found that the normal range of Evans index was 0.20 to 0.25, 0.25 to 0.30 represented early ventricular enlargement and value more than 0.30 suggested ventricular enlargement. Evans index was one of the older ventriculographic indices which represented ventricular volume [14], hence widely used in the diagnosis of idiopathic normal pressure hydrocephalus, in the assessment of outcome of patients with shunt placement which is the primary mode of treatment [25]. In the present study mean Evans index was 0.252± 0.031, which was due to shrinkage of brain parenchyma, compensated by the increase in size of ventricles.…”
Section: Indicessupporting
confidence: 50%
“…He found that the normal range of Evans index was 0.20 to 0.25, 0.25 to 0.30 represented early ventricular enlargement and value more than 0.30 suggested ventricular enlargement. Evans index was one of the older ventriculographic indices which represented ventricular volume [14], hence widely used in the diagnosis of idiopathic normal pressure hydrocephalus, in the assessment of outcome of patients with shunt placement which is the primary mode of treatment [25]. In the present study mean Evans index was 0.252± 0.031, which was due to shrinkage of brain parenchyma, compensated by the increase in size of ventricles.…”
Section: Indicessupporting
confidence: 50%
“…Treatments recommended in the guidelines are VP shunt (ventriculoperitoneal shunt), VA shunt (ventriculoatrial shunt) and, if the patient shows no spinal canal stenosis and adequate CSF passage, LP shunt (lumboperitoneal shunt) (Marmarou, Bergsneider, Klinge, Relkin, & Black, 2005; Marmarou, Black, Bergsneider, Klinge, & Relkin, 2005; Marmarou, Black, Bergsneider, Klinge, & Relkin, 2005; Mori et al., 2012; Relkin, Marmarou, Klinge, Bergsneider, & Black, 2005; Sasaki et al., 2008; Toma, Holl, Kitchen, & Watkins, 2011). In this survey, LP shunt was the first choice (55.1%) of treatment for iNPH, followed by VP shunt (43.2%), suggesting that, at present, these two shunt operations are the mainstays for the treatment of iNPH.…”
Section: Resultsmentioning
confidence: 99%
“…The Evans Index was measured as the maximal width of the frontal horns of the bilateral ventricles to the maximal width of the internal diameter of the cranium on the basis of the x dimension. 9,10 The z-Evans Index was defined as the maximum z-axial length of the frontal horn, which was between the roof and bottom of the larger lateral ventricle to the maximum cranial z-axial length at the base of the posterior end of the foramen of Monro (Fig 4). In the same procedure, the y-Evans Index was defined as the maximum y-axial length between the posterior end of the foramen of Monro and the anterior end of the frontal horns to the maximum cranial y-axial length.…”
Section: D Coordinates Of the Bilateral Ventriclementioning
confidence: 99%
“…[1][2][3][4][5] However, some studies using volumetric analysis suggested that it was not a sufficient linear index for evaluating ventricular enlargement. 9,10 In recent years, a T2-weighted 3D spin-echo se-quence with sampling perfection with application-optimized contrasts by using different flip angle evolutions (SPACE sequence; Siemens, Erlangen, Germany) has been developed. [11][12][13][14] This volumetric sequence enables the decrease of specific absorption rate limits and a scan of the whole brain in a single slab and a true isotropic 3D data record with high resolution (voxel size Յ 1 mm 3 without interpolation).…”
mentioning
confidence: 99%